The Profitability of Fish Production by Co-Operative Society Members in Rivers State, Nigeria (Global Journal of Management and Business Research, 2020)
Fishing is predominantly the major occupation of Rivers State people, and there is the general belief that it has the prospects of booming their welfare. Unfortunately, the vibrancy and growth of the sector are yet to be realized due to certain constraints. Thus, most fishermen had to join the various cooperative societies as a way of mitigating the challenges of fishing business in order to harness the profitability of the sector. This study investigated the profitability of fish production among members of cooperative societies in Rivers State, Nigeria.
Keywords: fish production; fishing; fishermen; cooperative fish farmers; cooperative societies